KEMATIAN IBU DI INDONESIA (Analisis Data Survei Demografi dan Kesehatan Indonesia Tahun 1994-2007) - Arsyad, Syahmida S. (GIZI INDONESIA, 2009)
MATERNAL MORTALITY IN INDONESIA(AN ANALYSIS OF THE 1994-2007 IDHS DATA)Maternal mortality is one of the main indicators of a community’s health status. It also reflects theperformance of a country’s health system. Almost 90 percents of maternal mortality can be preventedby, among others, maternal health care programs, nutrition improvement programs, family planningprograms, and increasing women’s education level. This paper has two objectives. The first objectiveis to describe maternal mortality ratios and its trend which are obtained from the 1994, 1997, 2002-2003 and 2007 Indonesia Demographic and Health Survey (IDHS) results. The second objective is toanalyze factors influencing maternal mortality ratios in Indonesia. This information would be usefulfor policy makers to improve maternal health care programs. The 1994 IDHS used both direct andindirect methods, known as ”sisterhood method”, while the 1997, 2002-2003, and 2007 IDHS usedonly direct method to estimate maternal mortality rates and ratios. The surveys’ results show adeclining trend in maternal mortality for the five-year period prior to the surveys. The maternalmortality ratios according to the 1994, 1997, 2002/03 and 2007 IDHS are 390, 334, 307, and 228 per100,000 live births respectively. However, due to high sampling errors, it is difficult to concludewhether a decline in maternal mortality ratios has occurred during the last 20 years. The 1994, 1997,2002-2003 and 2007 IDHS results also demonstrate the effects of maternal health care programs onmaternal mortality ratios. Therefore, this paper concludes that the quality of maternal health careprograms need to be improved, which include antenatal, delivery and postnatal care, and also familyplanning programs.Keywords: Maternal mortality rate and ratio, Indonesia Demographic and Health Survey, maternalhealth care programs.